Prevalence study of Legionella spp. contamination in ferries and cruise ships - Azara, Antonio; Piana, Andrea; Sotgiu, Giovanni; Dettori, Marco; Deriu, Maria Grazia; Masia, Maria Dolores; Are, Bianca Maria; Muresu, Elena (BMC public health, 2006)
In the last years, international traffic volume has significantly increased, raising the risk for acquisition of infectious diseases. Among travel-associated infections, increased incidence of legionellosis has been reported among travellers. Aim of our study was: to describe the frequency and severity of Legionella spp. contamination in ferries and cruise ships; to compare the levels of contamination with those indicated by the Italian ministerial guidelines for control and prevention of legionellosis, in order to assess health risks and to adopt control measures. A prevalence study was carried out on 9 ships docked at the seaports of northern Sardinia in 2004. Water samples were collected from critical sites: passenger cabins, crew cabins, kitchens, coffee bars, rooms of the central air conditioning system. It was performed a qualitative and quantitative identification of Legionella spp. and a chemical, physical and bacteriological analysis of water samples. Forty-two percent (38/90) water samples were contaminated by Legionella spp.. Positive samples were mainly drawn from showers (24/44), washbasins (10/22). L. pneumophila was isolated in 42/44 samples (95.5%), followed by L. micdadei (4.5%). Strains were identified as L. pneumophila serogroup 6 (45.2%; 19 samples), 2-14 (42.9%), 5 (7.1%) and 3 (4.8%). Legionella spp. load was high; 77.8% of the water samples contained > 10(4) CFU/L. Low residual free chlorine concentration (0-0.2 mg/L) was associated to a contamination of the 50% of the water samples. Legionella is an ubiquitous bacterium that could create problems for public health. We identified Legionella spp. in 6/7 ferries. Microbial load was predominantly high (> 10(4) CFU/L or ranging from 10(3) to 10(4) CFU/L). It is matter of concern when passengers are subjects at risk because of Legionella spp. is an opportunist that can survive in freshwater systems; high bacterial load might be an important variable related to disease's occurrence. High level of contamination required disinfecting measures, but does not lead to a definitive solution to the problem. Therefore, it is important to identify a person responsible for health safety in order to control the risk from exposure and to apply preventive measures, according to European and Italian guidelines.